Cementing material based on synergy of electrolytic manganese residues and multiple solid wastes and preparation method
By washing electrolytic manganese slag with water and mechanical powdering, and mixing it with other solid waste and sodium hydroxide, gelling materials are formed, and the problems of electrolytic manganese slag and solid waste treatment are solved, and the effects of resource utilization and environmental protection are achieved.
Patent Information
- Application Number
- CN202411912662.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The prior art is difficult to effectively deal with electrolytic manganese slag and other solid waste, resulting in environmental pollution and waste of resources. At the same time, the high amount of cement used in cementitious materials leads to high energy consumption and carbon dioxide emissions.
By washing the electrolytic manganese slag and mechanical powdering, combining slag powder, steel slag powder and silica fume, first mixing is performed using sodium hydroxide, and then second mixing with water to form a solid waste-based slurry, and the gelled material is obtained through preliminary and re-curing.
The harmless treatment and resource utilization of electrolytic manganese slag has been achieved, the leaching concentration of ammonia nitrogen and manganese in the gelling materials has been reduced, the sewage discharge standards have been met, and environmental pollution and energy consumption have been reduced.
Smart Images

Figure CN119683883A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of environmental materials, and in particular to a gelling material based on electrolytic manganese slag in coordination with a variety of solid wastes and a preparation method thereof. Background Art
[0002] In the production process of metallic manganese, electrolytic manganese slag is produced; currently, the main method of treating electrolytic manganese slag is to pile it in the open air or landfill it. However, electrolytic manganese slag contains manganese and other heavy metal ions, as well as ammonia nitrogen compounds. During the process of rainwater scouring or infiltration, harmful substances will flow into the natural environment, including soil, rivers and groundwater sources, thus posing a potential threat to the ecosystem and human health. Therefore, the development of new technologies to achieve the harmless treatment of electrolytic manganese slag and its high-value comprehensive utilization is of great significance for environmental protection and resource conservation.
[0003] Cementitious materials are an indispensable part of construction projects, and the most commonly used one is silicate cement, which is widely used in various structures due to its excellent hydraulic hardness and adaptability. However, the production of cement is an energy-intensive process that leads to a large amount of carbon dioxide emissions, which has a negative impact on global climate change. Therefore, it has become urgent to find ways to reduce the use of cement.
[0004] The Chinese invention patent application with publication number CN114605123A discloses a manganese slag-based ultra-high performance composite cementitious material and concrete material, wherein the cementitious material includes 60-65% cement, 11-15% electrolytic manganese slag powder, 16-24% silica fume, 3-5% limestone powder, and 2-5% calcium sulfate whisker. Although electrolytic manganese slag is used to replace part of the cement in the patent application, the amount of cement is still as high as 60-65%, and other solid wastes are not processed in large quantities, and how to reduce the ammonia nitrogen leaching concentration and manganese leaching concentration of the cementitious material is not explored.
[0005] In view of this, it is necessary to provide a cementitious material and a preparation method based on electrolytic manganese slag and multiple solid wastes to solve or at least alleviate the technical problems of how to omit the use of cement in cementitious materials, and how to reduce the ammonia nitrogen leaching concentration and manganese leaching concentration of cementitious materials based on solid waste materials. Summary of the invention
[0006] The main purpose of the present invention is to provide a cementitious material and a preparation method based on electrolytic manganese slag and multiple solid wastes, aiming to solve the above-mentioned technical problems of how to omit the use of cement in the cementitious material, and how to reduce the ammonia nitrogen leaching concentration and manganese leaching concentration of the cementitious material based on solid waste materials.
[0007] To achieve the above object, the present invention provides a method for preparing a cementitious material based on electrolytic manganese slag and multiple solid wastes, comprising the steps of:
[0008] S1, sequentially washing and mechanically pulverizing the electrolytic manganese slag to obtain electrolytic manganese slag powder; first mixing the electrolytic manganese slag powder, slag powder, steel slag powder, silica fume, and sodium hydroxide to obtain a solid waste mixed raw material;
[0009] The mass ratio of the electrolytic manganese slag powder, the slag powder, the steel slag powder, the silica ash, and the sodium hydroxide is 15-25:35-45:25-35:8-12:2-6;
[0010] S2, mixing water and the solid waste mixed raw material for a second time at a mass ratio of 0.4-0.6:1 to obtain a solid waste-based slurry;
[0011] S3, performing preliminary curing and secondary curing on the solid waste-based slurry in sequence to obtain a cementitious material.
[0012] Furthermore, the method for obtaining the electrolytic manganese slag powder includes: subjecting the electrolytic manganese slag to the water washing treatment and drying to obtain the washed electrolytic manganese slag; subjecting the washed electrolytic manganese slag to the mechanical powdering treatment and then passing through a 200-mesh sieve to obtain the sieve-less material as the electrolytic manganese slag powder.
[0013] Furthermore, the water washing process comprises: stirring the electrolytic manganese slag and water at a mass ratio of 1:5-20 for 12-30 hours, and filtering to obtain the washed manganese slag mud to be dried.
[0014] Furthermore, the mechanical powderization treatment includes: crushing and vibrating the washed electrolytic manganese slag in sequence, and the vibration time is 2-6 minutes.
[0015] Furthermore, the second mixing includes: sequentially performing a first stirring and a second stirring on water and the solid waste mixed raw material;
[0016] The first stirring has a rotation speed of 40-80 r / min and a duration of 80-200 s; the second stirring has a rotation speed of 100-150 r / min and a duration of 80-200 s.
[0017] Furthermore, the first stirring and the second stirring are performed at an interval of 10-30s; during the interval, the stirring is stopped.
[0018] Furthermore, the temperatures of the initial curing and the secondary curing are both 18-30°C, and the humidity is both 80-99%; the duration of the initial curing is not less than 1 day, and the duration of the secondary curing is not less than 3 days.
[0019] Furthermore, before the initial curing, the solid waste-based slurry is injected into a mold; after the initial curing is completed, the mold is demoulded, and then the secondary curing is performed.
[0020] Furthermore, the chemical composition of the electrolytic manganese slag includes silicon dioxide, calcium oxide, and aluminum oxide; the electrolytic manganese slag contains ammonia nitrogen and soluble divalent manganese.
[0021] The present invention also provides a gelling material based on electrolytic manganese slag and multiple solid wastes, which is prepared by any of the gelling material preparation methods described above.
[0022] Compared with the prior art, the present invention has at least the following advantages:
[0023] The present invention prepares a cementitious material based on electrolytic manganese slag in collaboration with a variety of industrial solid wastes, realizes the harmless treatment and resource utilization of the electrolytic manganese slag, and disposes of a variety of industrial solid wastes; the present invention omits the use of cement in the cementitious material, and can efficiently solidify ammonia nitrogen and Mn (II) in the electrolytic manganese slag, meeting the first-level standard of the "Comprehensive Sewage Discharge Standard", avoiding pollution to the surrounding environment and occupying a large amount of land resources.
[0024] The raw materials used in the present invention are mainly solid waste, which is easy to obtain, can reduce the impact of waste on the environment, reduce the pressure of landfills, and reduce the risk of secondary pollution. The preparation method of the present invention is simple and efficient, can absorb a large amount of solid waste, and can be easily applied on a large scale in industrial solid waste yards such as manganese slag; the present invention can reduce the cost of building materials, and the obtained cementitious material has good mechanical properties, which can improve the durability and strength of concrete structures. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0026] Figure 1 is the XRD diagram of the original electrolytic manganese slag in Example 1 of the present invention;
[0027] Figure 2 This is a physical picture of a solid waste-based cementitious material test block with a curing age of 28 days in Example 1 of the present invention;
[0028] Figure 3 The compressive strength bar graph of the solid waste-based cementitious material test blocks with a curing age of 3d, 7d, and 28d in Example 1 of the present invention;
[0029] Figure 4 This is a microscopic image of a solid waste-based cementitious material test block with a curing age of 7 days in Example 1 of the present invention;
[0030] Figure 5 The bar graph is a graph of ammonia nitrogen content in the water control (sampling test of ammonia nitrogen concentration in the leaching water), the positive control leachate, and the leachate of the solid waste-based cementitious material test block with a curing age of 3d, 7d, and 28d in Example 1 of the present invention;
[0031] Figure 6 This is a bar graph of the Mn(II) content of the positive control leachate and the leachate of the solid waste-based cementitious material test blocks with a curing age of 3d, 7d, and 28d in Example 1 of the present invention; the soluble Mn in the figure corresponds to Mn(II).
[0032] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0035] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any methods, equipment and materials of the prior art similar or equivalent to the methods, equipment and materials described in the embodiments of the present invention can also be used to implement the present invention.
[0036] It should be understood that the chemical composition of electrolytic manganese slag mainly includes silicon dioxide (SiO2), aluminum oxide (Al2O3) and calcium oxide (CaO), which are the key factors that determine whether it has gelling potential. Among them, silicon dioxide and aluminum oxide are the main sources of active silicates and aluminates, which can react with water to form a stable gelling structure during the hydration process; while calcium oxide helps to adjust the pH value of the system, promote the hydration reaction, and in some cases, it can also participate in the hydration reaction to form a strong hydration product. Due to the presence of the above active ingredients, electrolytic manganese slag exhibits good gelling properties, making it a potential alternative to traditional cementitious materials, especially in the preparation of high-performance concrete and environmentally friendly building materials.
[0037] Slag (blast furnace slag), steel slag and silica fume are all by-products in the industrial production process. The present invention utilizes electrolytic manganese slag, blast furnace slag, steel slag and silica fume in combination to complement each other to form substances required for the hydration stage of cementitious materials, while absorbing a variety of industrial solid wastes, recycling them harmlessly and applying them to the construction field.
[0038] The present invention provides a method for preparing a gelling material based on electrolytic manganese slag and multiple solid wastes, comprising the steps of:
[0039] S1, sequentially washing and mechanically pulverizing the electrolytic manganese slag to obtain electrolytic manganese slag powder; mixing the electrolytic manganese slag powder, slag powder (blast furnace slag powder), steel slag powder, silica ash and sodium hydroxide to obtain a solid waste mixed raw material; the mass ratio of the electrolytic manganese slag powder, the slag powder, the steel slag powder, the silica ash and the sodium hydroxide is 15-25:35-45:25-35:8-12:2-6, specifically 20:40:30:10:4.
[0040] The method for obtaining the electrolytic manganese slag powder includes: washing the electrolytic manganese slag, drying it to obtain the washed electrolytic manganese slag; mechanically pulverizing the washed electrolytic manganese slag, then passing it through a 200-mesh sieve, and taking the undersize as the electrolytic manganese slag powder; the electrolytic manganese slag powder can be understood as a mechanically modified electrolytic manganese slag raw material. In addition, in the present invention, the slag powder is the undersize after passing through a 200-mesh sieve, the steel slag powder is the undersize after passing through a 200-mesh sieve, and the silica ash is the undersize after passing through a 200-mesh sieve.
[0041] The water washing treatment process comprises: stirring the electrolytic manganese slag and water at a mass ratio of 1:5-20 for 12-30h or 12-24h, and filtering to obtain the water-washed manganese slag sludge to be dried; preferably, stirring the electrolytic manganese slag and water at a mass ratio of 1:8-12 for 20-30h, and filtering to obtain the water-washed manganese slag sludge; specifically, stirring the electrolytic manganese slag and water at a mass ratio of 1:10 for 24h, and vacuum filtering to obtain the water-washed manganese slag sludge.
[0042] The drying process comprises: drying the washed manganese slag mud at 105-110° C., specifically 105° C., until the moisture content is ≤1%; the drying time can be 6-48 hours, specifically 12 hours.
[0043] The mechanical pulverization treatment comprises: crushing and vibrating the washed electrolytic manganese slag in sequence; the vibration time is 2-6 minutes, preferably 3 minutes; the vibration can be performed in a vibration mill.
[0044] As a further description of the electrolytic manganese slag, the slag, the steel slag and the silicon ash:
[0045] In the present invention, the chemical composition of the electrolytic manganese slag includes silicon dioxide, calcium oxide, and aluminum oxide in the form of oxides, or the chemical composition of the electrolytic manganese slag includes silicon dioxide, calcium oxide, aluminum oxide, magnesium oxide, ferric oxide, potassium oxide, manganese oxide, sodium oxide, and sulfur trioxide; further, the chemical composition of the electrolytic manganese slag includes: 20-50% silicon dioxide, 10-25% calcium oxide, 5-15% aluminum oxide, 1- 8% magnesium oxide, 2-12% ferric oxide, 1-5% potassium oxide, 1-5% manganese oxide (MnO), 1-5% sodium oxide, and 20-40% sulfur trioxide; further, the electrolytic manganese slag contains 25-35% silicon dioxide, 10-20% calcium oxide, 5-10% aluminum oxide, 1-3% magnesium oxide, 5-8% ferric oxide, 2-3% potassium oxide, 2-3% manganese oxide (MnO), 1-2% sodium oxide, and 25-35% sulfur trioxide.
[0046] The electrolytic manganese slag used in the present invention is derived from Dongfang Mining in Huayuan County, Xiangxi Autonomous Prefecture, Hunan Province; in the present invention, sulfuric acid and ammonia water are added in the electrolytic manganese production process, and the filter residue is electrolytic manganese slag after multiple filter pressing; therefore, the electrolytic manganese slag contains ammonia nitrogen and soluble divalent manganese, and both ammonia nitrogen and soluble divalent manganese can be dissolved in water. That is, in the present invention, the electrolytic manganese slag is derived from the production process of electrolytic manganese, and sulfuric acid and ammonia water are introduced into the production process of electrolytic manganese.
[0047] In the present invention, ammonia nitrogen and soluble divalent manganese are not included in the chemical composition analysis of electrolytic manganese slag, but the leaching concentrations of ammonia nitrogen and soluble divalent manganese are analyzed separately; the reason is that since the characterization means X-ray fluorescence spectrometer (XRF) is mainly used to detect the element composition and content in the substance, the elements attached to the surface of the detection substance will not be detected, and the ammonia nitrogen involved in the present invention is brought by the ammonia reagent in the process of slag sample production, so it will not be reflected in the XRF detection result; since the characterization means X-ray fluorescence spectrometer (XRF) is mainly used to detect the element composition and content in the substance, the elements attached to the surface of the detection substance will not be detected, the soluble divalent manganese involved in the present invention is brought by sulfuric acid dissolving manganese carbonate or sulfuric acid dissolving manganese dioxide in the process of slag sample production, so it does not belong to MnO in the XRF detection result.
[0048] In the present invention, the electrolytic manganese slag is crushed and soaked in water at a solid-liquid ratio of 1g:10mL for 24h at 20-30°C (specifically room temperature) and under shaking conditions, and the solid and liquid are separated after soaking; the ammonia nitrogen (NH4 + -N) leaching concentration is 350-450 mg / L, and the soluble divalent manganese (Mn 2+ ) leaching concentration is 850-950 mg / L; specifically, the ammonia nitrogen leaching concentration of the electrolytic manganese slag is 392.96 mg / L, and the soluble divalent manganese leaching concentration of the electrolytic manganese slag is 896.65 mg / L.
[0049] In the present invention, the electrolytic manganese slag powder and water are immersed in water at a solid-liquid ratio of 1g:10mL, the immersion time is 24h, the immersion is carried out at 20-30°C (specifically room temperature) and under shaking conditions, and the solid-liquid separation is carried out after the immersion; the ammonia nitrogen leaching concentration of the electrolytic manganese slag powder is 45-55mg / L, and the soluble divalent manganese leaching concentration of the electrolytic manganese slag powder is 150-160mg / L; specifically, the ammonia nitrogen leaching concentration of the electrolytic manganese slag powder is 51.84mg / L, and the soluble divalent manganese leaching concentration of the electrolytic manganese slag powder is 155.45mg / L.
[0050] In the present invention, the slag powder is derived from the blast furnace ironmaking process; the chemical composition of the slag powder includes, by weight percentage and in the form of oxides: 20-40% silicon dioxide, 35-55% calcium oxide, 10-20% aluminum oxide, 5-15% magnesium oxide, 0-1% ferric oxide, 0-1% potassium oxide, 0-1% manganese oxide (MnO), 0-1% sodium oxide, and 0-5% sulfur trioxide; further, the slag powder contains 25-30% silicon dioxide, 40-46% calcium oxide, 10-15% aluminum oxide, 5-10% magnesium oxide, 0.1-1% ferric oxide, 0.2-1% potassium oxide, 0.1-1% manganese oxide (MnO), 0.3-1% sodium oxide, and 1-5% sulfur trioxide.
[0051] In the present invention, the steel slag powder is derived from the steelmaking process of the steel industry; the chemical composition of the steel slag powder includes, by weight percentage and the form of oxides: 10-20% silicon dioxide, 35-55% calcium oxide, 5-15% aluminum oxide, 5-15% magnesium oxide, 10-20% ferric oxide, 0-1% potassium oxide, 0-5% manganese oxide (MnO), 0-1% sodium oxide, and 0-3% sulfur trioxide; further, the steel slag powder contains 10-20% silicon dioxide, 40-50% calcium oxide, 5-10% aluminum oxide, 7-13% magnesium oxide, 10-20% ferric oxide, 0.1-1% potassium oxide, 1-5% manganese oxide (MnO), 0.1-1% sodium oxide, and 0.5-3% sulfur trioxide.
[0052] In the present invention, the silica ash is derived from the process of high-temperature smelting of industrial silicon and ferrosilicon in an industrial electric furnace; the chemical composition of the silica ash includes, by mass percentage and in the form of oxides: 90-99% silicon dioxide, 0-3% calcium oxide, 0-1% aluminum oxide, 0-1% magnesium oxide, 0-1% ferric oxide, 0-1% potassium oxide, 0-1% manganese oxide (MnO), 0-1% sodium oxide, and 0-1% sulfur trioxide; further, the silica ash contains 90-99% silicon dioxide, 0.5-3% calcium oxide, 0.1-1% aluminum oxide, 0.1-1% magnesium oxide, 0.1-1% ferric oxide, 0.1-1% potassium oxide, 0.001-0.1% manganese oxide (MnO), 0.1-1% sodium oxide, and 0.1-1% sulfur trioxide.
[0053] S2, mixing water and the solid waste mixed raw material for a second time at a mass ratio of 0.4-0.6:1 to obtain a solid waste-based slurry; preferably, the mass ratio of water and the solid waste mixed raw material is 0.43-0.47:1; specifically, mixing water and the solid waste mixed raw material for a second time at a mass ratio of 0.45:1 to obtain a solid waste-based slurry.
[0054] In the present invention, the second mixing includes or is: sequentially performing a first stirring and a second stirring on water and the solid waste mixed raw material; the second mixing can be performed in a pure pulp mixer.
[0055] The first stirring speed is 40-80 r / min, and the duration is 80-200 s; preferably, the first stirring speed is 50-70 r / min, and the duration is 100-150 s; specifically, the first stirring speed is 60 r / min, and the duration is 120 s.
[0056] The second stirring has a rotation speed of 100-150 r / min and a duration of 80-200 s; preferably, the second stirring has a rotation speed of 110-130 r / min and a duration of 100-150 s; specifically, the second stirring has a rotation speed of 120 r / min and a duration of 120 s.
[0057] The first stirring and the second stirring are performed at an interval of 10-30 seconds, specifically 20 seconds; during the interval, the stirring is stopped.
[0058] S3, performing preliminary curing and secondary curing on the solid waste-based slurry in sequence to obtain a cementitious material.
[0059] In the present invention, the temperature of the initial curing condition and the secondary curing condition are both 18-30°C, and the humidity is both 80-99%; preferably, the temperature of the initial curing condition and the secondary curing condition are both 18-22°C, and the humidity is both 93-97%; the duration of the initial curing is not less than 1d, specifically 1d; the duration of the secondary curing is not less than 3d or not less than 7d or not less than 28d, and can further be 3-28d or 7-28d or 26-30d.
[0060] In the present invention, before the initial curing, the solid waste-based slurry is injected into the mold; after the initial curing, the mold is demolded, and then the secondary curing is performed. That is, the solid waste-based slurry is injected into the mold for molding, initial curing, demolding, and then secondary curing. When the solid waste-based slurry is injected into the mold, it is compacted by vibration; the initial curing and the secondary curing are performed in a constant temperature and humidity chamber.
[0061] The present invention also provides a gelling material based on electrolytic manganese slag and multiple solid wastes, which is prepared by any of the gelling material preparation methods described above.
[0062] The present invention utilizes the gelling activity of electrolytic manganese slag and cooperates with multi-source solid waste to achieve gelling under the action of alkali excitation, and solidifies the ammonia nitrogen and soluble divalent manganese in the original electrolytic manganese slag. In this process, no cement needs to be added. While realizing the resource utilization of electrolytic manganese slag, the preparation cost and energy consumption are also reduced.
[0063] In the present invention, the mechanical properties of the cementitious material are as follows: 3d compressive strength is 5-15MPa, 7d compressive strength is 20-30MPa, and 28d compressive strength is 35-45MPa.
[0064] The cementitious material is crushed and soaked in water at a solid-liquid ratio of 1g:10mL for 24 hours at 20-30°C (specifically room temperature) and under shaking conditions, and the solid and liquid are separated after soaking; the ammonia nitrogen leaching concentration of the cementitious material is less than 15mg / L, and the Mn(II) leaching concentration of the cementitious material is less than 2mg / L. Further, the ammonia nitrogen leaching concentration of the cementitious material is 0.02-8.00mg / L, and the Mn(II) leaching concentration of the cementitious material is 0.01-0.10mg / L; further, the ammonia nitrogen leaching concentration of the cementitious material is 1.5-5.5mg / L or 1.5-2.5mg / L, and the Mn(II) leaching concentration of the cementitious material is 0.01-0.05mg / L.
[0065] The following are specific examples of the present invention:
[0066] Example 1
[0067] 1. The preparation steps of the gelling material are as follows:
[0068] S1, mixing the electrolytic manganese slag (original electrolytic manganese slag) and water in a mass ratio of 1:10 for 24 hours (water washing), and then filtering by vacuum filtration to obtain water-washed manganese slag mud; placing the water-washed manganese slag mud in an electric heated blast drying oven, and drying it at 105° C. for 12 hours to obtain water-washed electrolytic manganese slag.
[0069] The washed electrolytic manganese slag is crushed by a jaw crusher, and then placed in a vibration mill for vibration grinding for 3 minutes. After vibration grinding, it is passed through a 200-mesh sieve, and the material under the sieve is taken as electrolytic manganese slag powder.
[0070] The electrolytic manganese slag powder, blast furnace slag (blast furnace slag powder exceeding 200 mesh), steel slag (steel slag powder exceeding 200 mesh), silica fume (silicon fume exceeding 200 mesh) and sodium hydroxide are fully mixed in a mass ratio of 20:40:30:10:4 (first mixing) to obtain a solid waste mixed raw material.
[0071] The main chemical compositions and mass percentages of electrolytic manganese slag (original electrolytic manganese slag), blast furnace slag, steel slag and silica fume were analyzed by X-ray fluorescence analyzer (XRF), as shown in Table 1. In addition, the XRD analysis of original electrolytic manganese slag can be found in Figure 1 shown.
[0072] Table 1 Chemical analysis of solid waste (wt%)
[0073]
[0074] S2, mixing water and solid waste mixed raw materials for a second time at a mass ratio (water-cement ratio) of 0.45:1 to obtain a solid waste-based slurry.
[0075] In this embodiment, the second mixing is carried out in a pure slurry mixer; the second mixing is divided into a first stage and a second stage in sequence, the first stage is stirred at a slow speed of 60r / min for 120s, and the second stage is stirred at a fast speed of 120r / min for 120s. The stirring is stopped for 20s between the first and second stages.
[0076] S3, inject the solid waste-based slurry into a 20mm×20mm×20mm six-unit cubic mold, vibrate and compact it, and put it into a constant temperature and humidity chamber for curing. The setting parameters of the constant temperature and humidity chamber are temperature 20℃ and humidity 95%; after curing for 1d under the set parameters (initial curing), take out the test block for demoulding, and then put the test block into the constant temperature and humidity chamber again for curing with the same parameters (re-curing). The curing age is 3d, 7d, and 28d. After reaching the specified age, take out the test block to obtain a solid waste-based cementitious material test block (cementitious material based on electrolytic manganese slag and multiple solid wastes). Among them, the curing age refers to the time of re-curing; when the curing age is 3d, 7d, and 28d, the solid waste-based cementitious material test blocks are recorded as 3d test blocks, 7d test blocks, and 28d test blocks, respectively; for the actual picture of the 28d test block, see Figure 2 shown.
[0077] 2. Experimental results:
[0078] 1. The solid waste-based cementitious material specimens that have been cured to a specified age are tested for compressive strength using a T-type workbench testing machine, with a pressure application speed of 1 mm / min.
[0079] See also Figure 3 As shown in Figure 2, the compressive strength of the 3d test block is 12.26MPa, the compressive strength of the 7d test block is 24.23MPa, and the compressive strength of the 28d test block is 38.82MPa. The compressive strength increases with the increase of the curing age, and the compressive strength of the 28d test block meets the strength requirements of various building materials. In addition, see Figure 4 As shown, taking the 7d specimen as an example, a large amount of flocculent gel was generated in the 7d specimen.
[0080] 2. Crush the solid waste-based cementitious material specimens that have been cured to a specified age, use water as the leaching agent, and use a solid-liquid ratio of 1g:10mL to leach the cementitious material specimens (crush the original electrolytic manganese slag and use it as a positive control for leaching, and use the electrolytic manganese slag powder as an intermediate control), shake it in a shaker at room temperature for 24 hours, and obtain the leaching solution after filtration.
[0081] (1) Using the Nessler's reagent spectrophotometric method to determine ammonia nitrogen in water, the NH4 + -N to perform detection.
[0082] See also Figure 5 As shown in the results, the ammonia nitrogen concentration of the positive control (original electrolytic manganese slag) leachate was 392.96 mg / L; the ammonia nitrogen concentration of the 3d test block leachate was 5.16 mg / L, the ammonia nitrogen concentration of the 7d test block leachate was 2.28 mg / L, and the ammonia nitrogen concentration of the 28d test block leachate was 1.99 mg / L. The ammonia nitrogen concentration decreased with the increase of the curing age, and NH4 + -N was faster than the positive control leachate NH4 + -N concentration of 392.96mg / L, the removal rate is close to 99.5%. At the same time, the NH4 + -N concentrations did not exceed the first-level ammonia nitrogen standard of 15 mg / L in the "Integrated Sewage Discharge Standard" (GB8978-1996); in addition, after testing, the ammonia nitrogen leaching concentration of the intermediate control (electrolytic manganese slag powder) leaching solution was 51.84 mg / L.
[0083] (2) The Mn(II) content in the leaching solution was detected using an inductively coupled plasma emission spectrometer.
[0084] See also Figure 6 As shown in the results, the Mn(II) concentration of the positive control (original electrolytic manganese slag) leachate was 896.65 mg / L; the Mn(II) concentration of the 3d test block leachate was 0.04 mg / L, the Mn(II) concentration of the 7d test block leachate was 0.01 mg / L, and the Mn(II) concentration of the 28d test block leachate was 0.01 mg / L. Compared with the Mn(II) concentration of 896.65 mg / L in the positive control leachate, the solidification rate exceeded 99.9%. At the same time, the Mn(II) concentration of all cementitious material test block leachates did not exceed the first-level standard of soluble manganese of 2 mg / L in the "Integrated Sewage Discharge Standard" (GB8978-1996); in addition, the Mn(II) leaching concentration of the intermediate control (electrolytic manganese slag powder) leachate was tested to be 155.45 mg / L.
[0085] The leaching toxicity test results of the cementitious material test blocks showed that all indicators met the current national environmental protection standards, demonstrating the superior performance of the material in environmental protection; it confirmed that the product can effectively reduce the risk of soil and groundwater pollution in practical applications, reflecting its high ecological compatibility.
[0086] Comparative Example 1
[0087] 1. The preparation steps of the gelling material are as follows:
[0088] Compared with Example 1, in this comparative example, electrolytic manganese slag powder, blast furnace slag (blast furnace slag powder over 200 mesh), steel slag (steel slag powder over 200 mesh), silica ash (silicon ash over 200 mesh) and sodium hydroxide are fully mixed in a mass ratio of 50:20:20:10:0 to obtain a solid waste mixed raw material; and water and the solid waste mixed raw material are mixed for a second time in a mass ratio of 0.4:1 (water-cement ratio) to obtain a solid waste-based slurry; other conditions remain unchanged.
[0089] 2. Experimental results:
[0090] This comparative example adopts the same detection method as Example 1.
[0091] In this comparative example, the compressive strength of the 3d test block is 0.60 MPa, the compressive strength of the 7d test block is 1.12 MPa, and the compressive strength of the 28d test block is 2.42 MPa.
[0092] In this comparative example, the ammonia nitrogen concentration of the 3d test block leachate was 7.25 mg / L, the ammonia nitrogen concentration of the 7d test block leachate was 5.33 mg / L, and the ammonia nitrogen concentration of the 28d test block leachate was 5.12 mg / L.
[0093] In this comparative example, the Mn(II) concentration of the 3d test block leachate was 0.05 mg / L, the Mn(II) concentration of the 7d test block leachate was 0.04 mg / L, and the Mn(II) concentration of the 28d test block leachate was 0.02 mg / L.
[0094] The compressive strength of the product prepared in this comparative example does not meet the use standards and cannot be used as a basic material.
[0095] Comparative Example 2
[0096] 1. The preparation steps of the gelling material are as follows:
[0097] Compared with Example 1, the second mixing in this comparative example only performs the first stage of stirring (omitting the second stage of stirring), and other conditions remain unchanged; since the material prepared in this comparative example cannot be formed when demolded after 1 day of curing, this comparative example only obtains an unformed colloidal material after preliminary curing.
[0098] 2. Experimental results:
[0099] This comparative example adopts the same detection method as Example 1, and this comparative example detects the colloidal material.
[0100] In this comparative example, the prepared material was demoulded after 1 day of curing, and the material could not be formed and was a gel-like material with no compressive strength.
[0101] In this comparative example, the ammonia nitrogen concentration of the leachate corresponding to the colloidal material is 35.23 mg / L, which does not meet the first-level ammonia nitrogen standard of 15 mg / L in the "Comprehensive Sewage Discharge Standard" (GB8978-1996).
[0102] In this comparative example, the Mn(II) concentration of the leachate corresponding to the colloidal material is 12.47 mg / L, which does not meet the first-level standard of soluble manganese of 2 mg / L in the "Integrated Sewage Discharge Standard" (GB8978-1996).
[0103] Comparative Example 3
[0104] 1. The preparation steps of the gelling material are as follows:
[0105] Compared with Example 1, the curing conditions of the second curing in this comparative example are adjusted to curing in natural air without controlling the temperature and humidity, and other conditions remain unchanged.
[0106] 2. Experimental results:
[0107] This comparative example adopts the same detection method as Example 1.
[0108] In this comparative example, the compressive strength of the 3d test block is 11.45MPa, the compressive strength of the 7d test block is 16.37MPa, and the compressive strength of the 28d test block is 18.15MPa, which are lower than the standard curing compressive strength. The reason is that the humidity in the air is not high, and the cementitious material test blocks cannot have sufficient water for continuous hydration, and the degree of hydration is slow.
[0109] In this comparative example, the ammonia nitrogen concentration of the 3d test block leachate was 4.29 mg / L, the ammonia nitrogen concentration of the 7d test block leachate was 4.03 mg / L, and the ammonia nitrogen concentration of the 28d test block leachate was 3.95 mg / L;
[0110] In this comparative example, the Mn(II) concentration of the 3d test block leachate was 0.06 mg / L, the Mn(II) concentration of the 7d test block leachate was 0.04 mg / L, and the Mn(II) concentration of the 28d test block leachate was 0.04 mg / L.
[0111] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a cementitious material based on electrolytic manganese slag and multiple solid wastes, characterized in that: Includes steps: S1, sequentially washing and mechanically pulverizing the electrolytic manganese slag to obtain electrolytic manganese slag powder; first mixing the electrolytic manganese slag powder, slag powder, steel slag powder, silica fume, and sodium hydroxide to obtain a solid waste mixed raw material; The mass ratio of the electrolytic manganese slag powder, the slag powder, the steel slag powder, the silica ash, and the sodium hydroxide is 15-25:35-45:25-35:8-12:2-6; S2, mixing water and the solid waste mixed raw material for a second time at a mass ratio of 0.4-0.6:1 to obtain a solid waste-based slurry; S3, performing preliminary curing and secondary curing on the solid waste-based slurry in sequence to obtain a cementitious material.
2. The method for preparing a cementitious material according to claim 1, characterized in that: The method for obtaining the electrolytic manganese slag powder includes: subjecting the electrolytic manganese slag to the water washing treatment and drying to obtain the water-washed electrolytic manganese slag; subjecting the water-washed electrolytic manganese slag to the mechanical powdering treatment and then passing it through a 200-mesh sieve, and taking the sieve-under material as the electrolytic manganese slag powder.
3. The method for preparing a gelling material according to claim 2, characterized in that: The water washing treatment process comprises: stirring the electrolytic manganese slag and water at a mass ratio of 1:5-20 for 12-30 hours, and filtering to obtain the water-washed manganese slag mud to be dried.
4. The method for preparing a cementitious material according to claim 2, characterized in that: The mechanical powderization treatment includes: crushing and vibrating the washed electrolytic manganese slag in sequence, and the vibration time is 2-6 minutes.
5. The method for preparing a cementitious material according to claim 1, characterized in that: The second mixing comprises: sequentially performing a first stirring and a second stirring on water and the solid waste mixed raw material; The first stirring has a rotation speed of 40-80 r / min and a duration of 80-200 s; the second stirring has a rotation speed of 100-150 r / min and a duration of 80-200 s.
6. The method for preparing a cementitious material according to claim 5, characterized in that: The first stirring and the second stirring are separated by an interval of 10-30 seconds; during the interval, the stirring is stopped.
7. The method for preparing a gelling material according to claim 1, characterized in that: The temperatures for the initial curing and the secondary curing are both 18-30° C., and the humidity is both 80-99%; the duration of the initial curing is not less than 1 day, and the duration of the secondary curing is not less than 3 days.
8. The method for preparing a cementitious material according to claim 1, characterized in that: Before the initial curing, the solid waste-based slurry is injected into a mold; after the initial curing, the mold is demoulded and then the secondary curing is performed.
9. The method for preparing a gelling material according to claim 1, characterized in that: The chemical composition of the electrolytic manganese slag includes silicon dioxide, calcium oxide and aluminum oxide; the electrolytic manganese slag contains ammonia nitrogen and soluble divalent manganese.
10. A cementitious material based on electrolytic manganese slag and multiple solid wastes, characterized in that: The method for preparing the cementitious material is adopted as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Manganese slag-based ultrahigh-performance composite cementing material and concrete material
CN114605123A
Method for preparing concrete by taking manganese residue-steel residue-limestone powder as admixture
CN102329105A
Electrolytic manganese slag resource utilization process
CN104129937A
Baking-free archaized black brick based on electrolytic manganese slag, and preparation method and application thereof
CN112047702A
High-strength nickel slag-based solid waste cementing material and preparation method thereof
CN112608043A
Cited By
Electrolytic manganese residue-based cementitious material, method for preparing same and concrete
CN122608309A